THE EFFECT OF MIND MAPPING STRATEGY ON THE WRITING DESCRIPTIVE TEXT ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 01 KAMPAR UTARA - Hikmah, Alfi; ', Eliwarti; ', M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This pre-experimental research aimed to find out whether there is a significant effect of Mind Mapping Strategy on the writing descriptive text ability of the second year students of SMPN 01 Kampar Utara in the Academic Year 2016/2017. This research used one group pre-test and post-test design with six treatment meetings. The instrument used in this research was writing tests (pre-test and post-test). The population of this research was 103 eighth grade students of SMPN 01 Kampar Utara and the sample was class VIII A (25) students of SMPN 01 Kampar Utara. The data of this research were collected by writing tests of descriptive text. The data were analyzed using t-test formula. The results showed that the mean score of pre-test was 53.27, and the mean score of post-test was 70.1. Based on the data analysis, there was an increase the students’ averange score for pre-test (53.27) to post-test (70.1). Moreover from t-test, it was found that the t-obs (27.641 ) was higher than t-table (2.064). Therefore, the alternative hypothesis of this research was accepted and null hypothesis was rejected. This also means that teaching writing by using Mind Mapping Strategy was effective to improve the ability of students in writing Descriptive text.Key Words: Writing ability, mind mapping, descriptive text